MOBILE PHONE BRAND EQUITY AND PURCHASE INTENTION: THE MEDIATING EFFECT OF BRAND PREFERENCE - Sewanthy; Kennedy, F. B. (International Journal of Research -GRANTHAALAYAH, 2020)
The mobile phone industry is one of the major technological-based area that the fastest growing industry in the overall world. The purpose of the research report was to find out how the brand preference effect as a mediating variable between brand equity and purchase intention. According to the study, the researcher investigated the level, relationship, and impact of those variables. The study mainly considering the primary data and secondary data. Structured questionnaire was used as the method of data collection and there are 31 research questions. Among them five questions are consist with personal information of the respondent and other twenty-six questions are research information. The five likerts point scale was used which ranging from “strongly agree” to “strongly disagree”. It has been conducted a pilot test to test the reliability of the questionnaire and all the questions are reliable. Collected data were analyzed using SPSS computer package having the univariate and bivariate analysis. A sample of 204 respondents was selected for the study from mobile phone users in Trincomalee district Town and Gravets area. Convenience sample method used to make the sampling frame of the study and also quantitative research approach used for this study. The finding of the study reveals that the brand equity, brand preference and purchase intention were in high level among mobile phone users in Trincomalee district Town and Gravets area. There were high positive relationship among brand equity, brand preference and purchase intention in mobile phone users in Trincomalee district Town and Gravets area. The final objective showed that the positive impact of brand equity on purchase intention, positive impact of brand equity on brand preference and purchase intention, positive impact of brand preference on purchase intention and brand equity and brand preference positively impact on purchase intention. The mediating analysis reveals partial mediation by brand preference the relationship between brand equity and purchase intention.